Tenggerese traditional medicine of Indonesia: Existing practices and the botanical identification of medicinal plants - Nugraha, Ari Satia; Agustina, Riza Putri; Mirza, Syafi; Pratama, Antonius Nugraha Widhi; Triatmoko, Bawon; Rani, Dinar Mutia; Winarto, Naura Bathari; Nawiyanto, Nawiyanto; Wangchuk, Phurpa; Keller, Paul A (Ethnobotany Research and Applications, 2024)
Background: The Indonesian health care system comprises both modern and traditional medical systems; while they are not integrated, they have co-existed for decades. Traditional medical treatments continue to enjoy popularity nationwide, especially for people living in rural areas. Methods: We interviewed the traditional healers of the Tengger community (the last Hindu society in Java Island – Indonesia) and botanically identified their medicinal plants. The cross-sectional surveys were conducted based on an unstructured ethnopharmacology interview. Use Value (UV), Family Use Value (FUV), Infomart consensus factor (ICF) and Use-reports were derived as primary data. Results: Nineteen dukuns were identified and interviewed. The dukun (local healer) practiced both spiritual and physical medication (using medicinal plants and animals). There were 41 medicinal plants from 23 different families used for treating 17 ailments. The study revealed that although Tengger culture evolved from the Southeast Asian dominant Hindu Kingdom - Majapahit, only less than half of the species identified were contained in the PROSEA and Ayurvedic databases. Apium graveolens L., Causonis clematidea (F.Muell.) Jackes, Drymocallis arguta (Pursh) Rydb., Elaeocarpus longifolius Blume, Garcinia mangostana L., Rubus allegheniensis Porter, Tagetes tenuifolia Cav. were the most cited species. The scientific approach revealed the uses of A. gravelolens. G. mangostana, R. allegheniensis and T. tenuifolia. Conclusions: These findings revealed the medicinal potential of ethnopharmacology in the medicinal plants of Tengger however several medicinal plants required further scientific investigation. Keywords: Ethnopharmacology, Indonesia, Hinduism, Tengger, Medicinal plants